Da fala para a leitura em voz alta: variação linguística, tipos de leitura e desempenho na aprendizagem inicial da leitura de alunos do 3º ano do ensino fundamental - Sá, José Júnior de Santana (2019)
The literacy process is one of the most important periods of elementary school. For many children, it is the time when the first contact with writing begins. Learning to read in an autonomous way an alphabetic system is the needed skill for the development of learning. However, the last results from the National Assessment of Literacy (NAL) show that Brazilian students are finishing the stage of literacy consolidation without being able to read and comprehend simple texts. Because of that, Bortoni-Ricardo (2005) suggests that one of the factors related to lower class children’s poor performance in literacy is the fact that they face an unknown norm in school which is different from their vernacular. Therefore, when regarding the initial learning of reading, the dialectal differences between the learners and the literacy teacher must also be considered (FREITAG, 2011, 2013, 2015; FLÔRES, 2017, 2018). Studies have also verified that variable speech phenomena may be transposed to the reading, mostly the ones related to gradual traces, i. e., the ones that are present in the speech of almost all Brazilians, as the deletion of /d/ in the sequence /ndo/, the monophthongization, the diphthongization, and the /r/ in syllable coda(MACHADO, 2018b; AQUINO, 2011). In order to contribute with this discussion, in this research, we aim at identifying the occurrence of variable speech phenomena in the stylistic monitoring gradient and its relation to the kinds of reading of third grade elementary school students from the city school Gina Franco, located in São Cristóvão-SE. For that, we longitudinally tracked the group from May to December in 2017, documenting students’ spontaneous speech, their oral activities (narratives, description, and naming from visual stimuli), recordings of the reading aloud of written texts adequate to the group’s curriculum, and, finally, we administered a reading comprehension test similar to NAL. Based on the necessary conditions to the initial learning of reading skills (MORAIS; LEITE; KOLINSKY, 2013; MORAIS, 2013b;c) and from the recordings of the reading aloud, we identified students’ kinds of reading. We also analyzed the variable phenomena: the deletion of /d/ in the sequence /ndo/, monophtongization, ditongação, and the deletion of /r/ in syllable coda in three stylistic gradients: spontaneous speech, oral activities, and reading aloud. We found that the deletion of /d/ in the sequence /ndo/, the monophthongization, the diphthongzation, and the deletion of /r/ in syllable coda were recurrent both in the oral activities and in the spontaneous speech. In the reading aloud, the deletion of /d/ and the diphtongization presented higher percentage of non-occurrences than the monophthongization and the /r/ in syllable coda, which did not differ in the gradients spontaneous speech and oral activities.Concerning the kinds of reading, among the 21 students from the third grade of elementary school, we identified five kinds of reading: six students were classified in the alphabetical reading; six in the syllabic reading; only two in the word by word reading; and three students in the capable reading. We also identified four students in the non-reading profile. In relation to the comprehension test, we verified that there is a positive relation between the kind of capable reading, the word by word reading and the performance on the reading comprehension test concerning the scores and the number of right answers. The students whose kind of reading is in the most advanced levels (capable and word by word) are the ones who access the lexical route, which was evidenced by the recurrence of gradual traces in their reading aloud. These students were also the ones who got higher performance on the reading comprehension test, both in scores and in number of right answers. Therefore, we conclude that the presence of gradual traces in the reading aloud is a predictive clue of success in the initial learning of reading, and that from the reading profile a sociolinguistic trained teacher may identify the students who are not accessing the lexical route to the reading.